Association of Serum Vaspin and Adiponectin Levels with Renal Function in Patients with or without Type 2 Diabetes Mellitus - Meiyu Yan; Bin Su; Wenhui Peng; Liang Li; Hailing Li; Jianhui Zhuang; Yuyan Lu; Weixia Jian; Yidong Wei; Weiming Li; Shen Qu; Yawei Xu (Journal of Diabetes Research)
Vaspin and adiponectin are two adipocytokines with antidiabetic effects. Some studies reported that levels of adiponectin and vaspin were correlated with decreased glomerular filtration rate (FGR) and increased albuminuria. We therefore evaluated the vaspin and adiponectin levels in renal insufficiency (RI) patients with or without T2DM. Serum vaspin, adiponectin levels were measured in 416 subjects with or without T2DM. Analysis was made between groups divided by these subjects presence or absence of RI. We found that serum adiponectin level was significantly higher in nondiabetic patients with RI than in nondiabetic subjects without RI; however, there were no statistical differences between the diabetic patients with RI and without RI. In all the subjects, the serum adiponectin level was also higher in 50 individuals with RI than that in 366 subjects without RI. The serum vaspin levels showed no significant differences between the diabetic patients or nondiabetics subjects with RI and without RI. Contrary to adiponectin, the serum vaspin level was lower in 169 patients with T2DM than in 247 individuals without T2DM. Our data suggested that both of T2DM and renal insufficiency were correlated with the serum level of adiponectin. However, the serum vaspin levels showed no significant difference between the individuals with renal insufficiency and without renal insufficiency.